Extraordinary capture of a Randall's snapper Randallichthys filamentosus in the temperate south‐eastern Indian Ocean and its molecular phylogenetic relationship within the Etelinae. Issue 2 (29th October 2015) - Wakefield, C. B.; Moore, G. I.; Bertram, A. E.; Snow, M.; Newman, S. J.
Abstract : The capture of a rarely encountered Randall's snapper Randallichthys filamentosus (female, 587 mm fork length) from the upper continental slope ( c . 350 m) off the south coast of Western Australia ( c . 34·5° S; 122·5° E) in January 2014 represents its first record from the temperate Indian Ocean and a southern range extension. This record suggests that spawning of this predominantly tropical species may probably be occurring in the eastern Indian Ocean, considering the extensive, and unlikely, distance the progeny would have otherwise travelled from its typical distribution in the western and central Pacific Ocean.